Engineering Hierarchical Recognition‐Mediated Senolytics for Reliable Regulation of Cellular Senescence and Anti‐Atherosclerosis Therapy. (16th December 2022) - Xia, Yinghao; Li, Jili; Wang, Linlin; Xie, Yuqi; Zhang, Lili; Han, Xiaoyan; Tan, Weihong; Liu, Yanlan
Abstract: Precise regulation of vascular senescence represents a far‐reaching strategy to combat age‐related diseases. However, the high heterogeneity of senescence, alongside the lack of targeting and potent senolytics, makes it very challenging. Here we report a molecular design to tackle this challenge through multidimensional, hierarchical recognition of three hallmarks commonly shared among senescence, namely, aptamer‐mediated recognition of a membrane marker for active cell targeting, a self‐immolative linker responsive to lysosomal enzymes for switchable drug release, and a compound against antiapoptotic signaling for clearance. Such senolytic can target and trigger severe cell apoptosis in broad‐spectrum senescent endothelial cells, and importantly, distinguish them from the quiescent state. Its potential for in vivo treatment of vascular diseases is successfully illustrated in a model of atherosclerosis, with effective suppression of the plaque progression yet negligible side effects. Abstract : An aptamer‐senolytic molecular prodrug is developed for reliable regulation of vascular senescence through hierarchical recognition of three types of senescence‐related hallmarks. It can actively target and trigger cell‐specific apoptosis in senescent endothelial cells caused by various stimuli, while keeping silent in non‐senescent cells, contributing to effective inhibition effects on the senescence burden‐induced progress of atherosclerosis.